THE MEANING OF MAHABBAH ACCORDING TO IBN 'ARABI'S PERSPECTIVE - Moch. Qasim Mathar; Barsihannor; Salahuddin; Falihin, Dalilul (Jurnal Diskursus Islam, 2022)
This paper reveals in-depth the concept of mahabbah based on Ibn 'Arabi's perspective. The type of research used in this paper was library research. This research revolved on studying the concept of Mahabbah according to Ibn 'Arabi by adjusting the qualitative research. The research method used by the author was descriptive with a philosophical approach. The Philosophical approach could also examine the structure of the basic ideas (fundamental ideas) formulated by the thinkers. Primary data sources were the works of Ibn 'Arabi, both in the form of books and papers. Secondary data sources were data in the form of books, papers, and articles relevant to the concept of Ibn 'Arabi, from various writings with the knowledge and concern about Ibn 'Arabi's thoughts, especially in the field of Sufism. The technique used by the author in collecting the data was the citation technique, which refers to quoting part or all of the data from various readings that relate to the problem studied. The writer carried out the data analysis. After collecting the data, the writer analyzed it based on the type, then connected one data to another. Next, interpreted the data based on the research principles, and described it using deductive and inductive thinking techniques. Based on Ibn 'Arabi's perspective, the results showed that mahabbah (love) could not be defined; love is difficult to understand. Love can only be found and lived in the deepest depths of the heart. However, it is undeniable that everyone can feel the beauty of love even if they cannot make an analogy of its ultimate. God loves His creatures as a form of manifestation of His al-wadud, al-rahman, al-rahim attributes. Love is the reason and motive for the universe's creation; It cannot separate Ibn' Arabi's theory about love from the doctrine of wahdat al-Wujud as the center of his Sufistic doctrine. It asserted that there are no lovers and beloved except Allah because all entities in nature are the manifestations (Tajalliyat) of the magnificence of Allah. Ibn 'Arabi said that the basis and cause of all love is magnificence. God loves his creatures because the creatures are magnificent. Meanwhile, humans love God because they see God’s magnificence. God is the great and the source of all fineness.